Social Issues of People with Special Needs in Modern Mass Media - Kurmanbayeva, Alma; Noda, Larisa; Danayeva, Nurlyaiym; Nogaibayeva, Zhibek; Kabylgazina, Klara (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
This research paper discusses the problem of social issues, especially the issues of people with intellectual disabilities and how modern mass media supports. Mainly one case study was represented from aspects working with people with ID. This study aimed to examine how the press represents people with intellectual disabilities and how it helps people with this problem. The study was conducted using the method of qualitative content analysis. The material for the report consisted of research. The survey covered the year 2016. The purpose of this qualitative study was to produce an overview of topics and practical recommendations that have been presented for teaching for students with intellectual disabilities. To represent the richness of this research area, the topic was purposely left broad, and the outline was made by focusing on the practical implications of research articles. These recommendations were identified, classified, synthesised, and evaluated. The implications for practice and research are presented based on the findings of this study This research is of significant value, as a contribution to the journalism science policy not only in Kazakhstan but abroad as well. It demonstrates that social issues of the problems of people with ID in modern mass media are widely discussed and are of great importance from the sight of an audience.